2017
DOI: 10.4103/0970-4388.206034
|View full text |Cite
|
Sign up to set email alerts
|

Association between family structure and oral health of children with mixed dentition in suburban Nigeria

Abstract: For this study population, the number of siblings and the birth rank increased the chances of having caries and use of fluoridated toothpaste, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 2 publications
3
24
0
3
Order By: Relevance
“…Indeed, the odds of dental caries of the students increased with their birth ranks. This was comparable with other studies (45,46). This result is due to the fact that the increase in the number of children in the family is likely to reduce the parental attention of children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, the odds of dental caries of the students increased with their birth ranks. This was comparable with other studies (45,46). This result is due to the fact that the increase in the number of children in the family is likely to reduce the parental attention of children.…”
Section: Discussionsupporting
confidence: 91%
“…This result is due to the fact that the increase in the number of children in the family is likely to reduce the parental attention of children. In addition, the number of children increase, the household expense increase; therefore, the possibility of receiving dental health care for children decrease and, subsequently, the probability of their dental caries increase (46).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with those of Wellappuli and Amarasena [9] who reported that a birth rank > 1 was significantly associated with dental caries experience in 3-5year-old children compared with children with a birth rank of 1. Recently, studies from Nigeria found more caries in children with three or more siblings compared to 0-2 siblings [10,23]. Previous studies have reported somewhat contradictory results concerning birth order and family size in relation to caries.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies in this area are small, and the subgroups of birth order vary. Although risk of dental caries in later-born children compared to first-born children has been found to be higher [9,10], conflicting results have also been reported [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…The few studies in this area are small, and the subgroups of birth order vary. Although risk of dental caries in laterborn children compared to first-born children has been found to be higher [9][10], conflicting results have also been reported [11][12].…”
Section: Introductionmentioning
confidence: 97%